A day that America will remember: flashbulb memory, collective memory, and future thinking for the capitol riots. Issue 5 (28th May 2023) - Cheriet, Nawël; Topçu, Meymune; Hirst, William; Bastin, Christine; Folville, Adrien
ABSTRACT : This study explores the topics of flashbulb memory, collective identity, future thinking, and shared representations for a public event. We assessed the memories of the Capitol Riots, which happened in Washington DC, on 6 January 2021. Seventy Belgian and seventy-nine American citizens participated in an online study, in which they freely recalled the unfolding of Capitol Riots and answered questions regarding their memory. Inter-subjects similarity of recalled details was analysed using a schematic narrative template (i.e., the event, the causes and the consequences). Results revealed that representations of the event, and its causes were more similar among Belgians compared to Americans, whereas Americans' representations of the consequences showed more similarity than Belgians'. Also, as expected, Americans reported more flashbulb memories (FBMs) than Belgians. The analysis underlined the importance of rehearsal through media and communication in FBM formation. This research revealed a novel relation between FBM and future representations. Regardless of national identity, participants who formed an FBM were more likely to think that the event would be remembered in the future, that the government should memorialise the event, and that a similar attack on the Capitol could happen in the future compared to participants who did not form FBM.